2018
DOI: 10.1152/japplphysiol.00897.2017
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle function during the progression of cancer cachexia in the male ApcMin/+ mouse

Abstract: While cancer-induced skeletal muscle wasting has been widely investigated, the drivers of cancer-induced muscle functional decrements are only beginning to be understood. Decreased muscle function impacts cancer patient quality of life and health status, and several potential therapeutics have failed in clinical trials due to a lack of functional improvement. Furthermore, systemic inflammation and intrinsic inflammatory signaling's role in the cachectic disruption of muscle function requires further investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 76 publications
(150 reference statements)
5
73
1
Order By: Relevance
“…Ageing and several chronic inflammatory diseases have been associated with preferential atrophy of type II muscle fibres in both humans and animal models (Carson et al., ; Lexell, ; Wang & Pessin, ). Researchers in our laboratory previously showed that the TA, which has primarily type IIb muscle fibres (Bloemberg & Quadrilatero, ), had reduced force and increased muscle fatigability in tumour‐bearing mice associated with increased STAT3 and SOCS3 activation (Murphy, Chee, Trieu, Naim, & Lynch, ; VanderVeen et al., ). Although more work is needed to understand the fibre‐type specificity of IL‐6, the COXIV and cytochrome c protein expression in the murine quadriceps muscle was susceptible to IL‐6 (Puppa et al., ), but was unchanged in the gastrocnemius (White et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ageing and several chronic inflammatory diseases have been associated with preferential atrophy of type II muscle fibres in both humans and animal models (Carson et al., ; Lexell, ; Wang & Pessin, ). Researchers in our laboratory previously showed that the TA, which has primarily type IIb muscle fibres (Bloemberg & Quadrilatero, ), had reduced force and increased muscle fatigability in tumour‐bearing mice associated with increased STAT3 and SOCS3 activation (Murphy, Chee, Trieu, Naim, & Lynch, ; VanderVeen et al., ). Although more work is needed to understand the fibre‐type specificity of IL‐6, the COXIV and cytochrome c protein expression in the murine quadriceps muscle was susceptible to IL‐6 (Puppa et al., ), but was unchanged in the gastrocnemius (White et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The mouse was place on the apparatus maintained at 37°C throughout the entirety of the procedure (Bonetto, Andersson, & Waning, ). Functional analysis of the TA muscle in situ , which maintains the host nerve and blood supply, has been described previously (VanderVeen et al., ). The sciatic nerve was exposed proximal to the knee and maintained using warmed mineral oil.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations